Genomic and precision medicine : Cardiovascular disease - Ginsburg, Geoffrey S.; Willard, Huntington F. (London : Elsevier/Academic Press, an imprint of Elsevier, 2018)
Genomic and Precision Medicine: Cardiovascular Disease, Third Edition, focuses on the applications of genome discovery on the broad spectrum of cardiovascular disorders. Each chapter is organized for the application of genomics and personalized medicine tools and technologies to a) Risk Assessment and Susceptibility, b) Diagnosis and Prognosis, c) Pharmacogenomics and Precision Therapeutics, and d) Emerging and Future Opportunities in the field.--
Family health history and health risk assessment for cardiovascular disease in health care -- Personalized lifestyle medicine -- Lipoprotein disorders -- Metabolic syndrome -- Hypertension -- Novel approaches to cardiovascular diagnostics : focus on coronary artery disease and myocardial infarction -- Hypertrophic cardiomyopathy in the era of genomic medicine -- Genomics to predict risk of coronary artery disease -- Genomics-guided antithrombotic therapy for acute coronary syndromes -- Heart failure : impact of genetics and genomics -- Arrhythmia genomics -- Genetics and genomics of peripheral arterial disease -- Genetic basis of congenital heart disease -- Perioperative genomics -- Genomics of ischemic stroke and prospects for clinical applications -- Cardiovascular pharmacogenetics.
Preceded by Genomic and personalized medicine / edited by Geoffrey S. Ginsburg and Huntington F. Willard. 2nd ed. 2013. (2 volumes).
Includes bibliographical references and index.
Keywords: Cardiovascular system -- Diseases; Cardiovascular system -- Diseases -- Genetic aspects; Medical genetics; Genomics; Cardiovascular Diseases -- drug therapy; Cardiovascular Diseases -- genetics; Cardiovascular Agents -- therapeutic use; Precision Medicine; Cardiovascular system -- Diseases; Cardiovascular system -- Diseases -- Genetic aspects; Genomics; Medical genetics